Institutionalization of Pancasila Values in the Formation and Evaluation of Sexual Violence Regulations in University - Yuni Priskila Ginting; Fransiskus Xaverius Wartoyo (Faculty of Law, Universitas Pekalongan, 2023)
The institutionalization of handling sexual violence in tertiary institutions has the authority to carry out evaluations and assessments that Permendikbudriset No. 30 of 2021 concerning the Prevention and Handling of Sexual Violence in the University Environment is or is not in accordance with Pancasila values. To find and understand what values are contained in the Pancasila precepts which can become a guiding instrument in the formation and evaluation of Permendikbudriset No. 30 of 2021 a statutory approach is taken in normative legal research and a qualitative approach in empirical legal research, using secondary information from the legal field. The results of the study show that legal instruments can be used as a reference in the formation and evaluation of sexual violence regulations in tertiary institutions that are in accordance with Pancasila values.